Iodine status and associations with feeding practices and psychomotor milestone development in six‐month‐old South African infants - Osei, Jennifer; Baumgartner, Jeannine; Rothman, Marinel; Matsungo, Tonderayi M.; Covic, Namukolo; Faber, Mieke; Smuts, Cornelius M. (Wiley, 2017)
Iodine is important for normal growth and psychomotor development. While infants below 6 months of age receive iodine from breast milk or fortified infant formula, the introduction of complementary foods poses a serious risk for deteriorating iodine status. This cross‐sectional analysis assessed the iodine status of six‐month‐old South African infants and explored its associations with feeding practices and psychomotor milestone development. Iodine concentrations were measured in infant (n = 386) and maternal (n = 371) urine (urinary iodine concentration [UIC]), and in breast milk (n = 257 [breast milk iodine concentrations]). Feeding practices and psychomotor milestone development were assessed in all infants. The median (25th–75th percentile) UIC in infants was 345 (213–596) μg/L and was significantly lower in stunted (302 [195–504] μg/L) than non‐stunted (366 [225–641] μg/L) infants. Only 6.7% of infants were deficient. Maternal UIC (128 [81–216] μg/L; rs = 0.218, p < 0.001) and breast milk iodine concentrations (170 [110–270] μg/kg; rs = 0.447, p < 0.0001) were associated with infant UIC. Most infants (72%) were breastfed and tended to have higher UIC than non‐breastfed infants (p = 0.074). Almost all infants (95%) consumed semi‐solid or solid foods, with commercial infant cereals (60%) and jarred infant foods (20%) being the most common solid foods first introduced. Infants who reported to consume commercial infant cereals ≥4 days weekly had significantly higher UIC (372 [225–637] μg/L) than those reported to consume commercial infant cereals seldom or never (308 [200–517] μg/L; p = 0.023). No associations between infant UIC and psychomotor developmental scores were observed. Our results suggest that iodine intake in the studied six‐month‐old infants was adequate. Iodine in breast milk and commercial infant cereals potentially contributed to this adequate intake.